One with you - Day, Sylvia (New York St. Martin's Griffin, 2016)
The finale to the crossfire saga finds Gideon and Eva fighting for their marriage, trying to keep their vows even when ugly secrets have been revealed
Series numeration from www.goodreads.com
1
Keywords: Man-woman relationships -- Fiction; Marriage -- Fiction; Erotic fiction; Romance fiction